Chemical and isotopic analysis in the investigation of glazes from Northern China and the Middle East, 7th-14th centuries AD - Shen, Jingyi (2017)
Both Chinese and Islamic glazed ceramics played a significant role in the history of ancient ceramic production. Moreover, it was innovation in glazes that made the Chinese and Islamic ceramics constantly innovative in various categories with different manufacturing techniques. This study applies chemical and isotopic analyses to investigate the manufacturing techniques and provenances of different types of glazes from Northern China and the Middle East, and extends the use of Sr isotopic analysis to investigate raw materials and glaze recipes used to making lime/alkaline glazes in Northern China and the Middle East for the first time.